Neglecting democracy in education policy: A-F school report card accountability systems - Murray, Kevin; Howe, Kenneth R. (Education Policy Analysis Archives, 2017)
Sixteen states have adopted school report card accountability systems that assign A-F letter grades to schools. Other states are now engaged in deliberation about whether they, too, should adopt such systems. This paper examines A-F accountability systems with respect to three kinds of validity. First, it examines whether or not these accountability systems are valid as a measure, that is, do these systems validly measure school quality? Second, it examines whether or not they are valid as a policy instrument. or, how far do A-F accountability systems fulfill the stated aims of their proponents—empowering parents, providing “simple” and “common sense” measures of educational quality, and so on? Finally, it examines whether or not A-F systems are valid as a democratic framework:, how well do these systems align with the broader goals of educating students for democratic citizenship and of incorporating parents and community members in democratic deliberation about policies for their public schools? The paper concludes that A-F accountability systems are invalid along each of these lines, and provides recommendations for democratically developing and implementing criteria for school assessment.